2004
DOI: 10.1161/01.cir.0000143626.16576.51
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor Receptor-2 or Tie-2 on Peripheral Blood Cells Defines Functionally Competent Cell Populations Capable of Reendothelialization

Abstract: Background— Receptor tyrosine kinases that include vascular endothelial growth factor (VEGFR)-1, VEGFR-2, and Tie-2 regulate cardiovascular development and physiological and pathological angiogenesis. We were interested in the phenotypic and functional characterization of peripheral blood cells expressing these receptors and their therapeutic potential in vascular injury. Methods and Results— VEGFR-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 26 publications
6
65
0
1
Order By: Relevance
“…In the present study, we show that a substantial subpopulation of CD14 ϩ monocytes (20%) in human peripheral blood express Tie-2. These data agree with that of Nowak and colleagues (27) who reported previously Tie-2 ϩ expression on 2% of total PBMC, with the majority of these Tie-2 ϩ cells being monocytes. Similarly, we found negligible levels of Tie-2 on other mononuclear cells or neutrophils (27).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we show that a substantial subpopulation of CD14 ϩ monocytes (20%) in human peripheral blood express Tie-2. These data agree with that of Nowak and colleagues (27) who reported previously Tie-2 ϩ expression on 2% of total PBMC, with the majority of these Tie-2 ϩ cells being monocytes. Similarly, we found negligible levels of Tie-2 on other mononuclear cells or neutrophils (27).…”
Section: Discussionsupporting
confidence: 93%
“…Thus we chose these two markers as they would not involve mature endothelial cells or monocytes. Most importantly, previous studies showed that CD14 + KDR + cells exhibit the potential to differentiate into cells with endothelial characteristics both in vitro and in vivo (Nowak et al 2004;Elsheikh et al 2005). Our study showed CD14 + KDR + cells constituting approximately 2.02%±1.41% of the total population of monocytes in the blood, which is very closely to the observation of Elsheikh et al (2005) (2%±0.5%).…”
Section: Determinants Of Circulating Cd14 + -Epcs Levelssupporting
confidence: 87%
“…Oth- ers have shown the ability of transplanted EPCs to restore endothelial function in damaged vessels. 99,100 We have also demonstrated the suitability of EPC to seed prosthetic grafts. Seeding of EPCs led to rapid endothelialization of expanded polytetrafluoroethylene (ePTFE) grafts after carotid interpositional grafting.…”
Section: Endothelial Cell Therapy For Vascular Repair and Bioengineermentioning
confidence: 81%
“…[13][14][15][16][17][22][23][24]81,[97][98][99][100] Autologous EPC transplantation may be used to promote rapid re-endothelialization and restoration of homeostasis in blood vessels injured during revascularization procedures 22-24,97-100 or for seeding of prosthetic grafts, stents, or engineered blood vessels to create a bioactive endothelial layer. 22,23,97,98 We showed recently that transplantation of autologous PB-EPCs leads to rapid re-endothelialization of balloon-denuded rabbit carotid arteries, resulting in significant reduction of neointimal hyperplasia.…”
Section: Endothelial Cell Therapy For Vascular Repair and Bioengineermentioning
confidence: 99%